2021
DOI: 10.1038/s42003-021-02421-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic signatures associated with depression and predictors of antidepressant response in humans: A CAN-BIND-1 report

Abstract: One of the biggest challenges in treating depression is the heterogeneous and qualitative nature of its clinical presentations. This highlights the need to find quantitative molecular markers to tailor existing treatment strategies to the individual’s biological system. In this study, high-resolution metabolic phenotyping of urine and plasma samples from the CAN-BIND study collected before treatment with two common pharmacological strategies, escitalopram and aripiprazole, was performed. Here we show that a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…40 As depicted in Figure S1, QC samples were successfully grouped, compared to the total variability observed, confirming the analytical robustness. 37,41 The sample collected at D145 was considered as an outlier in this study and was subsequently excluded (Figure S1). A careful review of IS signals confirmed the stability of the retention time, peak area and the mass accuracy which remained below 5 ppm.…”
Section: Sample Preparationmentioning
confidence: 99%
“…40 As depicted in Figure S1, QC samples were successfully grouped, compared to the total variability observed, confirming the analytical robustness. 37,41 The sample collected at D145 was considered as an outlier in this study and was subsequently excluded (Figure S1). A careful review of IS signals confirmed the stability of the retention time, peak area and the mass accuracy which remained below 5 ppm.…”
Section: Sample Preparationmentioning
confidence: 99%
“…This heterogeneity presents a challenge to traditional biomarker and drug discovery research that is based on the binary classifications of diseases, such as DSM diagnosis; and given the wide range of phenotypes within diseases, this "topdown" approach to biomarker discover is imprecise at best. There may be advantages, therefore, to also incorporate a "bottom-up" strategy to identify relevant clinical phenotypes and associated biomarkers that will refine our understand of the pathophysiology underlying disease and ultimately develop personalized treatment approaches (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Title and abstract Title and abstract Of the studies evaluated in our review, 21 evaluated therapeutic approaches [10,13,14,[18][19][20][21]26,29,33,[36][37][38]40,43,[48][49][50]55,56,58]. One study assessed arms with bupropion, venlafaxine, and mirtazapine [36].…”
Section: Strobe Itemsmentioning
confidence: 99%
“…Of the studies evaluated in our review, 21 evaluated therapeutic approaches [ 10 , 13 , 14 , 18 - 21 , 26 , 29 , 33 , 36 - 38 , 40 , 43 , 48 - 50 , 55 , 56 , 58 ]. One study assessed arms with bupropion, venlafaxine, and mirtazapine [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation